Original paperAnaesthesia and postoperative pain analgesia in rheumatoid arthritis foot surgery patients - Lisowska, Barbara; Michalak, Cezary; Ćwiek, Renata; Małdyk, Paweł; Blachowska-Wasiutyńska, Bogumiła (Reumatologia/Rheumatology, 2006)
We present methods of orthopaedic surgery, techniques of anaesthesia and postoperative pain treatment for patients with rheumatoid arthritis scheduled for foot operations. We present general methods used and our experience. All orthopaedic procedures were undertaken at the Rheumoorthopaedic Clinic in 2005. The most common technique was regional anaesthesia. In 30% of cases continuous epidural analgesia was used for postoperative pain treatment. In the others cases we used alternative methods. We did not perform continuous peripheral nerve block forefoot surgery.